From Policy to Practice: How Institutions Shape McDonald’s Behavior in Indonesia - Aziz, Chairul Iqbal; Abrar, Habibul; Latif, Ikhwan Rahmatika; Risky, Aulia; Fahlevi, Reza (International Journal on Social Science, Economics and Art, 2025)
This paper examines how national institutional environments shape the behavior of multinational corporations, with a focus on McDonald’s operations in Indonesia. Using Institutional Theory as the primary analytical framework, the study examines how international businesses react to various institutional pressures, including formal regulations, religious mandates, and informal cultural expectations. Through a qualitative case study approach, the research finds that McDonald's modified its operations to adhere to domestic sourcing regulations, fulfill halal certification standards, and accommodate regional dietary preferences and social norms. These adaptations reflect broader processes of institutional negotiation and legitimacy-building that go beyond market strategy. This research contributes to the literature on institutional theory and public governance by illustrating how deeply embedded regulatory and normative systems in emerging economies shape the strategic and operational choices of multinational firms. The findings offer actionable insight for policymakers aiming to guide foreign business conduct through institutional design, and for companies seeking legitimacy and stability in governance-intensive settings. By showing how public policy instruments and societal expectations interact to form a dynamic institutional environment, the study demonstrates how governments in emerging economies can steer globalization in ways that reinforce national values and development priorities